Sometimes a great notion [videorecording (DVD)] - Newman, Paul, 1925-2008; Fonda, Henry, 1905-1982; Remick, Lee; Sarrazin, Michael, 1940-2011; Gay, John, 1924-2017; Foreman, John, 1925-1992; Kesey, Ken (Universal vault series., 2011)
"Based on the best-selling novel about a two-fisted Oregon lumber family, the story focuses on a family that bucks their close-knit timber community in order to deliver a shipment of logs in defiance of a strike. In the process, one man is killed, the family patriarch Henry (Henry Fonda) is injured, and the eldest son Hank (Paul Newman) almost loses his wife (Lee Remick) to his half brother (Michael Sarrazin). Filled with complex characters and issues that still resonate today, Sometimes a Great Notion is an intense portrait of life set against the backdrop of logging."--Container.